Digital transformation of human resource management processes and practices: a study of Slovak enterprises - Vanda Čirčová; Janka Beresecká; Patrik Boršoš; Eva Čapošová (Entrepreneurship and Sustainability Issues)
Digital transformation is currently essential for effective human resource (HR) management within organisations. This topic is particularly relevant in the context of the Fourth Industrial Revolution, which introduces new challenges and opportunities for HR processes while also emphasising the responsibility for sustainable development. Implementing digital tools in HR can enhance the efficient use of HR, reduce negative environmental impacts, and promote corporate social responsibility. This research aims to explore the current level of digital transformation in HR processes within Slovak organisations, focusing on the potential of digital technologies to contribute to sustainable and responsible business practices. The study was conducted through a quantitative survey distributed to 743 respondents from Slovak companies. The analysis focused on evaluating the degree of digital tool implementation in areas such as recruitment, training, onboarding, and employee evaluation. The survey results revealed that recruitment and selection processes are the most digitised, emphasising social media and employer branding. In the area of learning and development, online training and employee reskilling are predominant. However, many organisations still rely on basic digital tools, with less frequent implementation of innovative technologies such as AI or gamification. The findings of this study provide valuable insights into the state of HR digital transformation in Slovak organisations and highlight areas requiring further development and investment, particularly with a focus on enhancing sustainability and responsibility in HR management.